PERANAN SATUAN RESERSE KRIMINAL KEPOLISIAN RESOR KOTA PEKANBARU DALAM MENANGGULANGI TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR DI KOTA PEKANBARU - IVAN SILABAN; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Reservior has encouraged others to commit crimes, it does not, if no one is willing to accept the proceeds of crime. If this can't be fixed of course like any society very disturbing feat. Then this is the role of the police force in tackling crime reservior is indispensable because the criminal action have trasnasional reservior is made with a